Relationship between Work-Family Balance and Job Performance of Academics: A study on Selected National Universities in Sri Lanka - Vithanage, Vidyanee; Arachchige, B.J.H. (My University, 2015)
Work-family balance is a challenging issue for many working adults. As far as Sri Lanka is concerned employees’ awareness and perception about work-family balance is very limited in comparison to Western countries. Academics in Sri Lanka are no exceptions and they receive very little or no family-friendly support from universities as they struggle to achieve a balance between work and family with their never-ending workload. The main research objective of this study was to investigate the relationship between university academics’ work-family balance and job performance. Further this study aimed to find the dimensional impact of work-family balance on job performance of university academics. With the purpose of accomplishing the aforesaid objectives, a self administered survey was carried out among 200 university academics that belong to the University of Sri Jayawardenapura, University of Colombo, University of Kelaniya and the University of Ruhuna. The sample was selected based on simple random sampling from the management faculties of the respective universities. This research study has found a statistically significant positive relationship between work-family balance and job performance among academics. It was also found that a significant positive relationship existed between work-family balance dimensions and job performance. Multiple regression analysis revealed satisfaction balance as the major contributor to job performance. These results are useful to the university administration to make policies to increase academics’ work life and family life through adopting supportive work environment.
Keywords: Work-family balance; Time balance; Involvement balance; Satisfaction balance; Job performance